Characteristics of children attended in child care consultation (Research, Society and Development, 2020)
This study was developed in the area of child´s health. Objective: Characterize the epidemiological profile of children attended by childcare consultation, highlighting the demographic characteristics of childhood in the range would range from 0 (zero) to 2 (two) years. Method: The present study was developed in the first and second semester of 2019, in the City of Três Passos. It is a quantitative research of the documentary type that was evaluated 160 medical records of children attended by childcare consultation in the last two years. Results: Regarding the calendar of childcare consultations recommended by the Ministry of Health, information about birth, first consultation and last consultation. Regarding the first consultation 85 (53.1%) were aged 8 (eight) to 12 (twelve) months. Discussion: Growth and Child development is a period of countless acquisitions, physical, mental and social, called the child's development milestone. Conclusion: However, children from the City of Três Passos, aged 0 to 2 years and mostly male.